FOSTERING STUDENTS’ READING COMPREHENSION WITH COMIC STRIPS - Alimin; Bilqis Shofiyah; Happy Kusuma Wardani (Universitas Islam Ogan Komering Ilir Kayuagung, 2025)
This research investigates the role of comic strips in improving the ninth-grade students of MTs Al Karimi Gresik. By utilizing collaborative action research conducted in two cycles, 25 ninth-graders became the subject of this research. The data were collected through multiple instruments, including reading assignments, observation sheets, and field notes. The collected data were analyzed using quantitative methods to assess improvements in students' reading abilities and qualitative methods to describe the students' engagement in each meeting. The findings indicate that comic strips significantly improved students' reading comprehension, although some common barriers were identified, including vocabulary challenges, lack of motivation, and difficulties with narrative structure. The test results revealed a significant improvement in students' reading comprehension, from a mean score of 73 by the end of Cycle 1 to 84 by Cycle 2. These findings suggest that teachers can effectively utilize comic strips to foster student engagement in language learning and academic performance. Thus, using comic strips promotes the broader educational objective of fostering student-centered learning environments, supports longterm student engagement, and provides a creative solution to common instructional challenges in language learning